Screening of the chemical composition and bioactivity of Waldheimia glabra (Decne.) Regel essential oil. (11th November 2015) - Manzo, Alessandra; Musso, Loana; Panseri, Sara; Iriti, Marcello; Dallavalle, Sabrina; Catalano, Enrico; Scarì, Giorgio; Giorgi, Annamaria
Abstract: BACKGROUND: This research aimed at improving knowledge as to the chemical composition and the antibacterial and anti‐cancer activities of the essential oil of Waldheimia glabra, a wild plant from the Himalayan Mountains. RESULTS: The results obtained by GC‐MS showed that spathulenol, 9‐tetradecenol, thujopsene, α ‐thujone, santolina alcohol and terpinen‐4‐ol were the main constituents of Waldheimia glabra essential oil. These results were confirmed by HS‐SPME GC‐MS analysis that also reported high amounts of artemisia alcohol and camphor. Disc diffusion assay suggested a mild antibacterial activity against both Escherichia coli and Staphylococcus aureus . Finally, a dose–response correlation was observed between Waldhemia glabra essential oil concentration and viability of human breast adenocarcinoma cells MDA‐MB‐231 and MCF‐7. CONCLUSIONS: Together with the GC‐MS method, HS‐SPME GC‐MS proved to be a reliable technique to characterise the chemical composition of essential oil obtained from aromatic plants. Further studies will focus on W. glabra phytochemicals and their biological activity, in order to support traditional uses of the plant. © 2015 Society of Chemical Industry